2008
DOI: 10.1002/ijc.23215
|View full text |Cite
|
Sign up to set email alerts
|

Invasive breast cancer cells exhibit increased mobility of the actin‐binding protein CapG

Abstract: The CapG protein, a Gelsolin-related actin-binding protein, is expressed at higher levels in breast cancer, especially in metastasizing breast cancer, than in normal breast epithelium. Furthermore, it is known that an increased expression of the CapG protein triggers an increase in cell motility. According to in vitro experiments, it was supposed that it is the nuclear fraction of the protein, which causes the increase in cell motility. Here, we examined the dynamical distribution of the CapG protein within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 31 publications
3
47
0
Order By: Relevance
“…Studying protein dynamics inside the living cell provides an analytical tool to elucidate the spatiotemporal organization of cell nuclei, which may provide insights beyond mere description. In this context, the comparative FRAP analysis of CapG distribution in normal and neoplastic breast epithelial cells from our recent work (Renz et al 2007) may serve as an example: The CapG protein appears to be transported much faster into the nucleus of breast cancer cells and is far less immobilized in the nucleus of cancer cells than in normal breast epithelial cells on the timescale of minutes. Both the immobilized fraction of CapG within the nucleus and its import kinetics distinguish normal and cancer …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studying protein dynamics inside the living cell provides an analytical tool to elucidate the spatiotemporal organization of cell nuclei, which may provide insights beyond mere description. In this context, the comparative FRAP analysis of CapG distribution in normal and neoplastic breast epithelial cells from our recent work (Renz et al 2007) may serve as an example: The CapG protein appears to be transported much faster into the nucleus of breast cancer cells and is far less immobilized in the nucleus of cancer cells than in normal breast epithelial cells on the timescale of minutes. Both the immobilized fraction of CapG within the nucleus and its import kinetics distinguish normal and cancer …”
Section: Discussionmentioning
confidence: 99%
“…Normal breast epithelium cells exhibit a much higher fraction of immobilized component (Renz et al 2007). Given the fit uncertainty, the immobile fraction in the neoplastic cells is negligible for both the slow and the fast subgroup.…”
Section: Frapvbslow^kinetics Of Entire Capg Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…De Corte et al (2004) showed that CapG may modulate the invasive properties of MDCK-AZ, HeLa, and HEK293T cells. Renz et al (2008) also found that the import of CapG into the nucleus is increased in invasive breast cancer cells. Our results showed that reduction of CapG expression in A549 and H358 cells was accompanied by significantly impaired motility, especially under hypoxia.…”
Section: Discussionmentioning
confidence: 85%